Unusually high clarithromycin resistance in Mycobacterium abscessus subsp. abscessus isolated from human gastric epithelium - Chouhan, Deepak; Retnakumar, R. J.; Devi, T. Barani; Dharmaseelan, Sanjai; Alexander, Sneha Mary; Devadas, Krishnadas; Chattopadhyay, Santanu; Nair, Gopinath Balakrish; Pillai, Madhavan Radhakrishna (Frontiers in Microbiology, 2023)
Mycobacterium abscessus subsp. abscessus is a rapidly growing facultative intracellular pathogen that usually infects human lung and skin epithelium. Recently, we and another group have shown that it also has the potential to colonize human gastric epithelium, but its significance with respect to gastric diseases remains unclear. Although Helicobacter pylori still remains the only definite gastric pathogen, recent studies have shown that M. abscessus subsp. abscessus also has the potential to colonize human gastric epithelium. M. abscessus subsp. abscessus is known to exhibit multidrug resistance and clarithromycin has been used as the drug of choice. We aimed to determine the clarithromycin resistance profile of 117 (74 rough and 43 smooth) gastric M. abscessus subsp. abscessus strains and to detect the point mutations in rrl and erm (41) genes conferring the resistance. Our data showed 79.48% (19 smooth and 74 rough) of M. abscessus subsp. abscessus strains were resistant to clarithromycin (MIC90 ≤ 512 μg/mL), while 20.51% (24 smooth) were susceptible (MIC90 ≤ 8 μg/mL). Nucleotide sequence analysis of the rrl gene with reference strains of M. abscessus subsp. abscessus did not show any mutation that is relevant to the clarithromycin resistance. However, analysis of erm (41) gene showed that M. abscessus subsp. abscessus strains, which were susceptible to clarithromycin had C, C, G, and C at their nucleotide positions 28, 159, 238, and 330, respectively, while the resistant strains showed T, T, A, and A at the same positions. Based on antibiogram and sequence analysis data we recommend further studies involving genomic analysis to identify the other genes involved in high clarithromycin resistance in gastric M. abscessus subsp. abscessus along with the mechanisms involved.